Prevalence of the Use of Aspirin and Statins for Preventing Cardiovascular Events in the Colombian Population with Type 2 Diabetes Mellitus: Comparison of 2008 and 2018 - Manuel E. Machado-Duque; Diego Arturo Garcia; Melissa Hiromi Emura-Vélez; Andrés Gaviria-Mendoza; Jorge E. Machado-Alba (SAGE Publishing, 2021)
Background Type 2 diabetes mellitus (T2DM) greatly increases cardiovascular risk. Primary and secondary cardiovascular prevention lead to lower cardiovascular events, improved quality of life and lower costs related to complications. Objective To estimate the proportion of patients with T2DM undergoing drug therapy for cardiovascular prevention (aspirin and statins) in Colombia and to describe the change in patterns of use between 2008 and 2018. Methods This was a cross-sectional study comparing prescriptions for aspirin and statins in 2008 and in 2018 in outpatients diagnosed with T2DM. Records were obtained from a national drug claim database. The proportion of use of cardiovascular prevention drugs and antidiabetic drugs, medications for comorbidities and sociodemographic variables were analyzed for both periods. Results In total, 26 742 patients in 2008 and 188 321 in 2018 with a diagnosis of T2DM treated with antidiabetic drugs were identified, among whom 57.5% and 44.2% received aspirin and 44.9% and 60.2% received statins, respectively. The use of high-intensity statins increased from 1.1% in 2008 to 95.2% in 2018. The probabilities of receiving drugs in 2008 and in 2018 were higher for men (OR: 1.12, 95% CI: 1.06-1.17 and OR: 1.26, 95% CI: 1.23-1.28, respectively), for those persons over 75 years of age (OR: 6.5, 95% CI: 5.3-7.9 and OR: 5.8, 95% CI: 5.4-6.2) and for those who also received clopidogrel (OR: 5.8, 95% CI: 4.4-7.6 and OR: 2.2, 95% CI: 2.1-2.4). Conclusions The use of high-intensity statins in patients with T2DM has increased significantly in the last decade, which should reduce cardiovascular events, morbidity and mortality.